Pengaruh Sikap Spiritual Terhadap Kepercayaan Diri Mahasiswa Peserta Sidang Munaqasyah Pada Masa Pandemi Covid-19 - sukri situmeang; Syamsudin Kastoer (Sekolah Tinggi Agama Islam Publisistik Thawalib Jakarta, 2020)
The aims of this study was to determined the influence of spiritual Attitudes on the self confidence of students participating in the munaqasyah triall during the covid-19 pandemic. This research is based on the backround of the covid-19 pandemic where the munaqasyah trial was carried out on a limited basis by implementing strict health protocols. The method used in this research is survey method with correlation technique sampling. The Population in this research were all students of the primary school teacher education study program at the Thawalib Islamic high school, Jakarta. Research sample is taken by purposive sampling technique as many as 20 students who take munaqasyah triall. The Instruments in this study are non test questions on the sipiritual attitudes and self confidence scale. The results showed that there was a positive influence between spiritual attitudes on the self confidence of student participating in munaqasyah triall, where spiritual attitudes influence of 57,9% to student self confidence and 42,1% by other variable.